The Future of Housing: Policy Scenarios - Cournède, Boris (OECD Publishing, 2020)
By combining fresh estimates of housing supply and prices with recent long-term projections for their fundamental drivers such as population, income and interest rates, this paper produces scenarios for residential investment and real house prices up to 2050. For half of the covered countries, projected increases in house prices are large enough to outpace real incomes, thereby further eroding housing affordability. The paper illustrates and quantifies how housing policies can make a difference. Removing mortgage interest relief eases price pressures and can contribute to more affordable housing. Likewise, streamlining land-use governance and easing rental control can help unlock housing supply, make housing markets more efficient and, ultimately, housing more affordable
Keywords: Economics